Molecular detection and hematological profile of Trypanosoma evansi in livestock - NILA QUDSIYATI; RADEN WISNU NURCAHYO; DWI PRIYOWIDODO; SOEDARMANTO INDARJULIANTO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Qudsiyati N, Nurcahyo RW, Priyowidodo D, Indarjulianto S. 2024. Molecular detection and hematological profile of Trypanosoma evansi in livestock. Biodiversitas 25: 3154-3159. Trypanosoma evansi, which assaults a variety of hosts and is found around the world, and is the causative agent of Surra sickness. The greatest Surra outbreak occurred in Indonesia in 2010-2012, primarily in Sumba, killing about 2,000 animals. The research purpose is to confirm T. evansi infection in livestock and determine hematological parameters in naturally infected livestock compared to non-infected (control). This study used molecular and parasitological testing techniques to identify Surra illness in the field. The buffy coat technique, Polymerase Chain Reaction (PCR), and thin blood smear test are used in the research methodology. Hematological parameters (red blood cell count, hemoglobin concentration, mean cell volume, mean cell hemoglobin, mean cell hemoglobin concentration, red cell distribution width, and white blood cell count) were analyzed. According to the PCR results, out of 222 blood samples, only 1 horse blood sample from Sumba shows a positive result for T. evansi. PCR is the most effective diagnostic tool for trypanosomiasis. This was the first time T. evansi DNA was discovered in Konga Loko Hamlet, Karuni Village, Sumba, Indonesia.